Redes de supermercados da Paraíba : análise dos benefícios mútuos e indicadores de desempenho nas relações interorganizacionais - Bezerra, Wellington Laurentino (2025)
This study addresses business partnerships between suppliers and supermarkets, aiming to analyze the interorganizational relationships of supermarket networks located in the state of Paraíba. The research problem guiding the investigation seeks to answer how relationships involving mutual benefits impact on the characteristics of cooperation, interdependence, trust, and stability within supermarket networks. The methodology employed was a quantitative approach, utilizing the survey strategy, also known as a survey. Data were collected through structured questionnaires administered in person, yielding responses from 27 participants in the cities of Sapé, Guarabira, Solânea, Araçagi, Tacima, Galante, Mari, Pirpirituba, Santa Luzia, and João Pessoa. Data analysis was performed using descriptive statistics and Spearman correlation, allowing the identification of associations between the studied variables. The results show that the managers of supermarket network companies in Paraíba are men, aged between 31 and 40 years, holding higher education degrees, and with up to 10 years of professional experience. The companies, in turn, are medium-sized, focus on the regional market, and have been operating for less than 10 years. Furthermore, it was possible to identify the performance indicators used in supermarket networks. In the correlation analysis, it was possible to verify that mutual benefits between cooperation and interdependence highlight resource and task sharing as a competitive advantage, associating the growth of suppliers' sales with speed and the diversification of problem resolutions. Additionally, the reduction of costs and infrastructure sharing are correlated with task interdependence. In the second correlation, trust and stability stand out with mutual benefits. The growth of suppliers' sales is linked to technical skills, credibility, and long-term contracts. Cost reduction is associated with reliability, reputation, honesty, and communication. From the results, it was possible to conclude that interorganizational partnerships are essential for the efficiency of supermarket networks, directly influencing competitiveness. Furthermore, adopting aligned performance metrics and collaborative practices can maximize mutual benefits and promote the sustainable development of the sector in Paraíba.